Internships as intercultural learning: A thematic analysis of Taiwanese design students in Japan - Chen, Tin-Kai (Journal of International Students, 2025)
This study examined 42 Taiwanese design students’ cross-cultural learning during internships in Japan’s creative industry firm, funded by Taiwan’s Ministry of Education under the “Dream-Building Study Abroad” program. Through thematic analysis and expert-rated intensity scoring (0–5 scale), six themes emerged. The highest-rated themes were workplace challenges (M = 3.33), language and culture (M = 3.31), and life experience (M = 3.22). The music students rated policy critique significantly higher than the animation students did (p < .001). The study combined qualitative coding with quantitative comparison to propose improvements in cultural briefings, language training, and post internship reflection.